2016
DOI: 10.1002/piq.21216
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the Human Performance Technology Practitioner Relative to ISPI Human Performance Technology Standards and the Degree of Standard Acceptance by the Field

Abstract: A s a fi eld, human performance technology (HPT) can be defi ned as the systematic approach to analysis and improvement of productivity and competence of human performers, traditionally in work settings. And as is the case with professional knowledge and competency standards for instructional design practice (e.g., the International Board of Standards for Training, Performance and Instruction standards), similar standards of HPT knowledge have been provided by a number of professional societies oriented to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Participants noted a lack of sufficient time, access, and support to simply perform needs assessment. These findings align with earlier research which found that many solutions are implemented without reference to needs assessment, project sponsors do not value thorough assessments of need, and analysis to specify the features of a pre‐determined solution is often substituted for needs assessment (Carliner et al, 2015; Hoard & Stefaniak, 2016; Leigh et al., 2000; Watkins et al, 1998).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Participants noted a lack of sufficient time, access, and support to simply perform needs assessment. These findings align with earlier research which found that many solutions are implemented without reference to needs assessment, project sponsors do not value thorough assessments of need, and analysis to specify the features of a pre‐determined solution is often substituted for needs assessment (Carliner et al, 2015; Hoard & Stefaniak, 2016; Leigh et al., 2000; Watkins et al, 1998).…”
Section: Discussionsupporting
confidence: 86%
“…Finally, even when practitioners can approach needs strategically, they may be constrained by their job roles such that they cannot evaluate the results of the needs assessments they conduct. Hoard and Stefaniak (2016) noted that there is little empirical evidence evaluating the actual skills and knowledge of HPT practitioners against standard competencies accepted by the field. The authors surveyed HPT practitioners to determine their perceptions of the HPT standards published by the ISPI and their actual use of those standards in the workplace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the studies reporting insufficient knowledge of evaluative practices (Klimczak & Wedman, 1996; Sleezer et al, 1992, Guerra‐Lopez & Leigh, 2009; Chyung, 2015), employers have reported that novice instructional designers lacked the skills to conduct summative evaluations, create evaluation plans, and conduct pilot tests after instruction had been designed and developed (Villachica, Marker, & Taylor, 2010). Hoard and Stefaniak (2016) found that human performance technology practitioners benefited from the standardization of professional competencies as they reported attaining a high level of accomplishment in the competency standards set forth for their field; however, the study also reported that responsibilities for design implementation and evaluation events were delegated to others within the organization. Standardization of the evaluation process for the instructional‐design field could lead to a common understanding of evaluation through shared language, process, and, ultimately, data (Schatz, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%